Protecting life: Qur’anic interpretation in kma no. 91/2025 and pesantren child care - Abdul Wahid; Fairus Tamamah; Zayyana Hariva; Dwi Ratnasari (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
The protection of children in faith-based educational institutions has become an increasingly urgent concern in global safeguarding discourse, particularly in contexts where religious authority strongly shapes institutional norms and practices. This study critically investigates the integration of the Qur’anic principle of ḥifẓ al-nafs (protection of life) within the framework of the Ministry of Religious Affairs Decree (KMA) No. 91/2025 and its implications for strengthening child protection in pesantren. Employing a qualitative normative–interpretive design, the study integrates thematic Qur’anic exegesis with systematic policy analysis through a structured analytical matrix that maps ethical constructs onto policy components. The findings demonstrate that ḥifẓ al-nafs constitutes a multidimensional safeguarding paradigm encompassing the sanctity of life, prevention of harm, preservation of dignity, ethical responsibility, and institutional accountability, all of which are substantively reflected in the structural design of KMA No. 91/2025. However, the study identifies a critical gap in the absence of explicit theological articulation within the policy, which constrains its normative resonance and limits deep institutional internalization. This study is among the first to operationalize maqāṣid al-sharī‘ah as a dynamic analytical framework for evaluating contemporary policy, thereby bridging the divide between Islamic ethical theory and modern governance. The findings further suggest that effective safeguarding in pesantren requires not only regulatory alignment but also the integration of Qur’anic ethical narratives to foster ethical internalization beyond procedural compliance. Ultimately, this study redefines faith-based child protection by proposing a value-driven policy model that is both culturally embedded and globally relevant, offering a new paradigm for safeguarding in religious educational systems.